PELATIHAN APLIKASI AKUNTANSI MYOB UNTUK MENINGKATKAN KINERJA TENAGA KEPENDIDIKAN TERHADAP PELAYANAN ADMINISTRASI KEUANGAN DI STIPAK – MALANG - Tri Istining Wardani (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2020)
The objectives of this community service are: to provide training in the fields of science and technology, especially the MYOB accounting application to improve the performance of educational staff at STIPAK - Malang in providing financial administration services to the entire academic community. In addition, it is also to equip educational staff at STIPAK - Malang with science and technology knowledge that is in accordance with the times.This activity is divided into 2 parts, the first provides an introduction and explanation of the specifications of the MYOB Accounting application and its advantages in processing financial data sets through the Command Center which includes the Account, Banking, Sales, Time Billing, Purchase, Payroll, Inventory, and Card File modules. Continued on the material practicing the accounting process of MYOB damalm companies through each computer by working on several financial cases according to the theory previously studied.The results of the training evaluation show that the training runs smoothly and effectively, the training participants as educational staff who have the task of processing financial data at STIPAK - Malang get enrichment in science and technology that support financial data processing through MYOB Accounting application training.